Perancangan Sistem Informasi Enterprise Resource Planning Pada Proses Perekrutan Karyawan (Studi Kasus: Pt. Suryaprana Nutrisindo) - Risky Fauziah; Maulana Ardhiansyah (INFORMATIKA, 2022)
The system carried out by PT. Suryaprana Nutrisindo in recruiting and selecting employees is by conducting a trial for employees for three months and then signing a work contract. However, the company PT. Suryaprana Nutrisindo also uses workers from outsourcing. In the process of recruiting employees, the company is still doing everything manually by the Human Resources (SMD) division, starting from collecting psychological test files, to collecting data on prospective employees. The Human Resources Division oversees the recruitment process in accordance with the planned and objective stages. Failure in implementing the recruitment system will have an impact on the process of achieving company goals. Where optimal performance will be realized if the organization can choose employees who have the motivation and skills that are in accordance with their work and have conditions that allow them to work optimally (Denok Sunarsi, HUMAN RESOURCE SEMINAR, 2019).